Growth and Characterization of ULMA Single Crystals Doped with Ammonium Chloride. (31st March 2013) - Sivasankari, B.; Selvarajan, P.
Abstract : Single crystals of pure and ammonium chloride-doped urea L-malic acid (ULMA) were grown by slow evaporation technique. Many interesting results on several properties of ammonium chloride impurity added to ULMA single crystals have been observed and studied. The different morphology of ammonium chloride-doped ULMA crystals was noticed and the effect of ammonium chloride doping on the growth, optical, and hardness properties has been investigated. The presence of functional groups has been estimated by FTIR analysis. The lattice parameters of the grown crystals were studied by single crystal X-ray diffraction technique. Powder X-ray diffraction studies confirm the diffraction planes of the grown crystals. The UV-visible spectrum shows the cutoff wavelength at 220 nm. A study on the thermal properties has also been carried out. The NLO property of the grown crystals was confirmed by SHG studies.